Design and Development of Android-Based Mathematic Learning Application for Form 1 PT3 Students - Yong Weng Cheng, Yong Wai Sheng; ISMAIL, MOHD NORASRI BIN ISMAIL (Applied Information Technology And Computer Science, 2022)
Recently, mobile learning is a new trend to access learning content using mobile devices. However, there are insufficient educational apps on the market for the specific age group of students. At the same time, many secondary school students in Malaysia struggle with acquiring basic math skills and memorizing the formula. Therefore, the objectives of this project are (1) to design the content of an educational Mathematics learning app for Form 1 PT3 students based on the Malaysia Secondary School syllabus KSSM model, (2) to develop an educational Mathematics learning app on the Android mobile platform, (3) to test an educational Mathematics learning app to Form 1 PT3 students. The Mathematics learning app called MATH#f1 will employ multimedia elements such as learning videos and infographics to attract students to learn mathematics. Multimedia Mobile Content Development has been chosen as the development methodology for this project. MATH#f1 consists of seven modules: login, registration, profile, learning, formula, practice, and the quiz module. The user can learn the same knowledge as it learns from school, as the apps will provide step-by-step teaching to give a better understanding. Besides, Alpha and Beta testing have been carried out throughout the development process. The Beta testing results show more than 80% of positive feedback obtained from the target users. Therefore, it can be concluded that the MATH#f1 application can be used as a learning aid.